Cytotoxic and cytostatic activity of five new imidazotetrazine derivatives on breast cancer cell cultures MDAMB231, BT474, and MCF-7 - Ahmed Hamid Al-Humairi; Svetlana E. Sitnikova; Valery V Novochadov (Research Results in Pharmacology)
Introduction: The work presents the results of the study of new imidazotetrazine derivatives to establish the possibility of using them as anticancer agents, including for chemotherapy of metastatic breast cancer. The relevance of the work is due to the wide spread of oncological diseases and high cancer mortality, which dictates the need to constantly obtain cell lines and improve cultivation protocols for testing new antitumor drugs. The goal of this study is to check the potential of five new imidazotetrazine derivatives to become new antitumor drugs, in the scope of studying their cytotoxic and cytostatic activities on breast cancer cell cultures.